If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10n + 6 = 86 Reorder the terms: 6 + 10n = 86 Solving 6 + 10n = 86 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 10n = 86 + -6 Combine like terms: 6 + -6 = 0 0 + 10n = 86 + -6 10n = 86 + -6 Combine like terms: 86 + -6 = 80 10n = 80 Divide each side by '10'. n = 8 Simplifying n = 8
| 6k^2-43k+72=0 | | 2x^2-5+8= | | 1-(2Y+5)=4(Y-7)-6 | | x+2/3x=255 | | -8(2x-9)=20-12 | | 195-145= | | 41-13=4(x-7) | | 170+25= | | 48=2*w*4 | | -8x^2+50=0 | | 8x+15-(5x-2)= | | 2(3+2)=22 | | -2-2(N-3)-3N=21+3 | | (7x-6)(4x+9)=0 | | -15x-20=-13x+100 | | 8x+15-5x-2= | | -3u+4= | | -2-2(N-3)-3N=21+7 | | 13x-(5+7x)= | | X/2-85=3x/11+270 | | -10=10y-60 | | X=-36-7/10x | | 3+x=31-5/9x | | 4s+8=4 | | 2T+3=5-2T+6 | | 15h-24=36 | | 49=12+x/7 | | -60=-5x+5(-x+10) | | 4y+16=24 | | 9k^2= | | 7(-3+x)=4(3-x) | | M+4=2M-3 |